Endohedral Metallofullerenes : Fullerenes with Metal Inside. - Shinohara, Hisanori (Wiley, 2015)
Endohedral Metallofullerenes: Fullerenes with Metal Inside presents a comprehensive survey of the current state of knowledge on endohedral metallofullerenes, from preparation to functionalization, reactivity and applications. Following a brief historical overview, the book describes methods for synthesis, extraction, separation and purification, and provides an insight into the molecular and crystal structures. Subsequent chapters discuss various categories of endohedral metallofullerenes based on the encapsulated species, including carbides, nitrides, sulphides, oxides, non-metal and non-IPR.